Treatment of neovascular age-related macular degeneration with anti-vascular endothelial growth factor drugs: progress from mechanisms to clinical applications - Cheng, Shizhou; Zhang, Shu; Huang, Mingyan; Liu, Yuxuan; Zou, Xunyu; Chen, Xiaoming; Zhang, Zuhai (Frontiers in Medicine, 2024)
Neovascular age-related macular degeneration (nARMD) is an important cause of visual impairment and blindness in the elderly, with choroidal neovascularization in the macula as the main pathological feature. The onset of nARMD is closely related to factors including age, oxidative stress, and lipid metabolism. Vascular endothelial growth factor (VEGF) is an important factor contributing to nARMD as well as choroidal neovascularization and retinal leakage formation. At present, anti-VEGF therapy is the only treatment that improves vision and halts disease progression in most patients, making anti-VEGF drugs a landmark development for nARMD treatment. Although intravitreal injection of anti-VEGF drugs has become the first-line treatment for nARMD, this treatment has many shortcomings including repeated injections, poor or no response in some patients, and complications such as retinal fibrosis. As a result, several new anti-VEGF drugs are being developed. This review provides a discussion of these new anti-VEGF drugs for the treatment of nARMD.